2006
DOI: 10.1016/j.ijfoodmicro.2006.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A occurrence and formation in Portuguese wine grapes at various stages of maturation

Abstract: A total of 93 Portuguese grape samples destined for wine production were examined for the presence of ochratoxin A (OTA) and the OTA producing fungi Aspergillus carbonarius and A. niger aggregate. Samples came from 11 vineyards from four winemaking regions in the North and South of the Portuguese mainland, during the harvest seasons of 2001, 2002 and 2003. Grapes were examined at 3 maturation stages, from setting to the harvesting period, to evaluate when contamination with OTA producing fungi and OTA synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 18 publications
3
32
0
Order By: Relevance
“…Grape sample. Samples from 11 vineyards from four winemaking regions in the North and South of the Portuguese mainland, during the harvest seasons of 2001, 2002, and 2003 were assessed for ochratoxin A and fungi (Serra, Mendonca, & Venancio, 2006). Significant differences were observed in ochratoxin A content of grapes between 2002 and 2003 which may have been related to temperature, although isolation of ochratoxin A fungi were only '' insignificantly different" upon the application of statistics between 2001 and 2003.…”
Section: Fumonisinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grape sample. Samples from 11 vineyards from four winemaking regions in the North and South of the Portuguese mainland, during the harvest seasons of 2001, 2002, and 2003 were assessed for ochratoxin A and fungi (Serra, Mendonca, & Venancio, 2006). Significant differences were observed in ochratoxin A content of grapes between 2002 and 2003 which may have been related to temperature, although isolation of ochratoxin A fungi were only '' insignificantly different" upon the application of statistics between 2001 and 2003.…”
Section: Fumonisinsmentioning
confidence: 99%
“…with Portugal in Serra et al, 2006). The aim was to study the fungi associated with grapes and their ability to produce ochratoxin A on synthetic media.…”
Section: Fumonisinsmentioning
confidence: 99%
“…A previous study by Cabañes et al (2002) observed that A. carbonarius isolates produced maximum OTA on unmodified YES agar and Czapek yeast agar after about 14 days. In a recent study, Serra et al (2006) found that the levels of OTA produced by black Aspergillus strains on the grape juice medium were lower than those produced on Czapek yeast agar. The ability of yeasts isolated from wine-grapes of Turkey to inhibit OTA production by A. carbonarius were assessed both in YES medium and grape juice.…”
Section: Effect Of Yeast Strains On Ota Accumulationmentioning
confidence: 96%
“…Several works have studied ecophysiological factors affecting fungal growth and OTA production by Aspergillus section Nigri strains in grape-based medium [37][38][39][40]. A. niger and A. carbonarius present an optimum temperature for growth around 30-35 • C although maximum OTA production is reached at lower temperatures (15)(16)(17)(18)(19)(20) • C) closer to that found during night when OTA accumulation might occur. High water activity levels favor both growth and OTA production; therefore, rainfall close to harvest might potentiate toxin accumulation on grapes.…”
Section: Introductionmentioning
confidence: 99%